The Intention of Men Who Have Sex With Men to Participate in Voluntary Counseling and HIV Testing and Access Free Condoms in Indonesia. Issue 5 (September 2018) - Fauk, Nelsensius Klau; Sukmawati, Anastasia Suci; Wardojo, Sri Sunaringsih Ika; Teli, Margareta; Bere, Yoh Kenedy; Mwanri, Lillian
This study aimed to identify factors that influenced the intention of men who have sex with men (MSM) to participate in voluntary counseling and HIV testing (VCT) and in accessing free condoms. A qualitative inquiry using one-on-one in-depth interviews was conducted with MSM participants who were recruited using a purposive sampling technique. Data analysis was guided by a framework analysis for qualitative data by Ritchie and Spencer, and the Theory of Planned Behavior (TPB) framework was used to analyze the data. The findings were grouped into three themes—namely, (a) attitude encompassing knowledge about HIV/AIDS and HIV/AIDS services and the belief about the positive outcomes of the services; (b) subjective norms including support from MSM peers and family members and motivation to comply with the support; and (c) perceived behavioral control, which is associated with resource availability and having confidence and positive intention to participate in VCT and willingness to access free condoms. Findings indicated that personal, community, and structural factors were predictors to intention to accessing services. Interventions targeting large numbers of MSM population and further studies to understand what needs to be done by nongovernmental organizations and governmental institutions to halt the spread of HIV infections among MSM populations and increase their intention to use HIV/AIDS services are also recommended.